Leveraging QR technology for sustainable living in Alor Setar / Atikah Raihanah Amir ... [et al.] - Amir, Atikah Raihanah; Ayob, Zulkefle; Mt Akhir, Norizan; Zafran, Muhammad Harith; Mohd Nazry, Muhammad Nazmy Azhary (2024)
This study explores the innovative application of QR technology in promoting sustainable living in Alor Setar, Kedah, a region renowned for its picturesque paddy fields. By enhancing pedestrian infrastructure and incorporating digital innovations, this project aims to strike a balance between urban development and environmental conservation. By leveraging Quick Response (QR) codes, this project envisions creating interactive installations that enhance the pedestrian experience. These installations will provide Augmented Reality (AR) experiences offering educational and entertainment value. The primary objectives are twofold: to improve pedestrian amenities and to design sustainable facilities that foster social interaction and community engagement. The QR-coded sidewalks will guide residents and visitors through scenic routes, highlight cultural landmarks and local biodiversity, thereby encouraging walking as a mode of transport. AR experiences will overlay historical narratives and ecological insights into real-world views, enriching the understanding of Alor Setar's heritage and environmental significance. Additionally, this initiative seeks to create social hubs with QR-enabled installations that promote communal activities and local crafts. Ultimately, the integration of QR technology into Alor Setar's urban planning promises to create a model of sustainable living that can be replicated in other cities facing similar challenges.